2021
DOI: 10.3389/fsurg.2021.590245
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Outcome After Open Abdomen Treatment: Function and Quality of Life

Abstract: Background: Open abdomen treatment (OAT) is widely accepted to manage severe abdominal conditions such as peritonitis and abdominal compartment syndrome but can be associated with high morbidity and mortality. The main risks in OAT are (1) entero-atmospheric fistula (EAF), (2) failure of primary fascial closure, and (3) incisional hernias. In this study, we assessed the long-term functional outcome after OAT to understand which factors impacted most on quality of life (QoL)/daily living activities and the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…14 Another 9.09% developed a small bowel fistula. 10 A clear advantage noted in our study is how only 2.7% of the entire population had a fistula. It was also found to be significantly smaller in number than its occurrence in other techniques.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…14 Another 9.09% developed a small bowel fistula. 10 A clear advantage noted in our study is how only 2.7% of the entire population had a fistula. It was also found to be significantly smaller in number than its occurrence in other techniques.…”
Section: Discussionmentioning
confidence: 65%
“…Fifty-five percent of the patients with primary closure techniques developed an incisional hernia in a study conducted in Bonn, Germany. 10 Similarly, a study on the complications of using Bogota bags showed that 65.45% of the cases needed skin grafting or healing by the formation of granulation tissue, leading to the development of hernias in the future. 11 The overall incidence of incisional hernia after laparotomy was 9.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term complications in survivors of an open abdomen approach include large incisional hernias, which often require repair [51 ▪▪ ]. The ideal timing and method of repair remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between healing of the laparotomy wound and development of the above complications has thus been well established over the years. A variety of factors influencing the healing process have been identified with the intention to develop strategies to reduce post laparotomy complications: These factors can be grouped in three main categories, (a) patient related, (b) surgeon or surgical technique related and (c) material related ( 1 , 2 , 7 , 10 15 ) ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%